Enhancing Clinical Trials Through Synergistic Gamma Power Analysis - Honda, Sokichi; Matsumoto, Mitsuyuki; Tajinda, Katsunori; Mihara, Takuma (Frontiers in Psychiatry, 2020)
While the etiology of many neuropsychiatric disorders remains unknown, increasing evidence suggests that aberrant sensory processing plays a central role. For this class of disorders, which are characterized by affective, cognitive, and behavioral symptoms, electroencephalography remains the dominant tool for providing insight into the physiological- and molecular underpinnings of the disease state and predicting the effectiveness of investigational new drugs. Within the spectrum of electrical activity present in the CNS, high-frequency oscillations in the gamma band are frequently altered in these patient populations. Measurement of gamma oscillation can be further classified into baseline and evoked, each of which offers a specific commentary on disease state. Baseline gamma analysis provides a surrogate of pharmacodynamics and predicting the time course effects of clinical candidate drugs, while alterations in evoked (time-locked) gamma power may serve as a disease biomarker and have utility in assessing patient response to new drugs. Together, these techniques offer complimentary methods of analysis for discrete realms of clinical and translational medicine. In terms of drug development, comprehensive analysis containing aspects of both baseline and evoked gamma oscillations may prove more useful in establishing better workflow and more accurate criteria for the testing of investigational new drugs.